(3hJWHjbGJg GdeYGUQIs - (3YHGS CMeO eMeO(B, (3GdHGRs ((3YeGf(B:s (3OGQ GdfaGFS(B,s, 1999)
(3YbO GdUQa aj Gdabg GdESdGej heTQhYjJg,GQcGf YbO GdUQa hTQhWg,GdhcGdI hGdMhGdI hGdehGYOI aj GdUQa,GdJWHjbGJ GdeYGUQI ddUQa,GdUQa ceG JeGQSg GdeUGQa GdeYGUQIs
(3HHdhZQGajG U(B.228s
Keywords: (3GdHfhcs; (3Gdabg GdGSdGejs; (3GdfbhOs